2015
DOI: 10.17719/jisr.20154013942
|View full text |Cite
|
Sign up to set email alerts
|

Prison Tourism as a Form of Dark Tourism

Abstract: PRISON TOURISM AS A FORM OF DARK TOURISM Sevinç ASLAN * "Great and terrible is the castle. 300 iron gate, like a giant guards, handles bars depend on, and each of the mustache, the 10 men hanging many notorious inmates are. Signs in the guards dragons such as walking. God forbid, then sentenced to flight, but the bird even flew They do not." Evliya Çelebi on Sinop Fortress Prison, Seyahatname

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Türkiye'de hüzün turizmi kapsamında değerlendirilen cezaevleri ile ilgili çalışmalara bakıldığında bu çalışmayla paralel sonuçlara ulaşıldığı görülmektedir. Örneğin, Aslan (2015) hüzün turizminin bir türü olan cezaevi turizmi üzerine bir çalışma yapmıştır. Çalışmada Türkiye tarihinde cezaevlerinin ve savaş alanlarının önemli olduğu ve Sinop Cezaevi'nin yapısı ve tarihi önemi belirtilmiştir.…”
Section: Sonuç Ve Tartişmaunclassified
“…Türkiye'de hüzün turizmi kapsamında değerlendirilen cezaevleri ile ilgili çalışmalara bakıldığında bu çalışmayla paralel sonuçlara ulaşıldığı görülmektedir. Örneğin, Aslan (2015) hüzün turizminin bir türü olan cezaevi turizmi üzerine bir çalışma yapmıştır. Çalışmada Türkiye tarihinde cezaevlerinin ve savaş alanlarının önemli olduğu ve Sinop Cezaevi'nin yapısı ve tarihi önemi belirtilmiştir.…”
Section: Sonuç Ve Tartişmaunclassified
“…It has been observed that many studies have been carried out on dark tourism since then (e.g. Aslan, 2015;Cohen, 2011;Hartmann, 2014;Kang et al, 2012;Light, 2017;Miles, 2002;Podoshen, 2013;Podoshen, 2017;Stone and Sharpley, 2008;Stone, 2006;Stone, 2012;Strange and Kempa, 2003). Some researchers have examined dark tourism attractions (Miles, 2014), motivation factors in dark tourism (Podoshen, 2013), benefits of visiting a dark tourism site (Kang et al, 2012), dark tourism impact (Wang and Luo, 2018), and experience in dark tourism (Iliev, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bunlar arasında; Anıtkabir, Dolmabahçe Sarayı, Ulucanlar Cezaevi, 12 Eylül Utanç Müzesi, Sinop Kalesi Cezaevi, Yassı Ada (Demokrasi ve Özgürlükler Adası), Sarıkamış, Çanakkale Savaşı ve İnönü Savaşlarının yapıldığı alanlar ve Başkomutan Tarihi Milli Parkı en başta gelen örneklerdir (Kozak ve Kama, t.y. : 6-7;Kurnaz vd., 2013: 59;Aslan, 2015).…”
Section: Introductionunclassified